2017
DOI: 10.1094/cchem-11-16-0274-r
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Effect of Added Gluten on Dough Properties and Quality of Chinese Steamed Bread

Abstract: Cereal Chem. 94(5):827-833Glutens isolated from 15 soft red winter (SRW) wheat flours were added into a SRW wheat flour to obtain protein levels of 9.6 and 11.3% for determination of the qualitative effect of added gluten on the dough properties and quality of northern-style Chinese steamed bread (CSB). Sodium dodecyl sulfate sedimentation (SDSS) volume of the gluten source flour exhibited positive relationships with mixograph absorption, midline peak time (MPT), and midline peak value (MPV) of the glutenadded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…Addition of gluten in low protein flour has been proved to be able to improve viscoelasticity and extensibility of the dough (Ma & Baik, 2017). In this study, the formulated flour with 35% potato flour and 65% wheat flour was selected to be the basic flour.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of gluten in low protein flour has been proved to be able to improve viscoelasticity and extensibility of the dough (Ma & Baik, 2017). In this study, the formulated flour with 35% potato flour and 65% wheat flour was selected to be the basic flour.…”
Section: Resultsmentioning
confidence: 99%
“…Mace1 scored 9 or greater of 10 for appearance shape, color, stickiness, flavor, and texture. Subsequently, Ma and Baik (2017) found an increase in protein content from 9.6% to 11.3% by adding gluten resulted in improved CSB-specific volume and crumb structure. He, Liu, Pena, and Rajaram (2003) reported that protein content, gluten strength, and dough extensibility were positively related to volume and elasticity of CSB in 66 bread wheat flours of 9.6%-16.2% protein content.…”
Section: Sensory Quality Of Steamed Breadmentioning
confidence: 98%
“…Ma and Baik (2016) found that wheat flours with a protein content higher than 8.9% and medium/strong gluten strength produced good CSB quality. Subsequently, Ma and Baik (2017) found an increase in protein content from 9.6% to 11.3% by adding gluten resulted in improved CSB-specific volume and crumb structure. A score of 15 ± 0.02 for Mace1 was a result of a specific volume of 1.8 ml/g, and a score of 16 ± 0.04 for Mace2 was the result of specific volume of 1.9 ml/g.…”
Section: Sensory Quality Of Steamed Breadmentioning
confidence: 98%
See 2 more Smart Citations